Lymphatic Disease in Cardiology: The Forgettable One - Sidhi Laksono Purwowiyoto; Novi Anggriyani; Steven Philip Surya (Universitas Airlangga, 2020)
Before molecular medicine era, the lymphatic system was not getting enough attention in medicine world, especially in cardiovascular medicine. Our knowledge about lymphatic system is far left behind compare to vascular system. Many believes lymphatic function is isolated in regulate interstitial fluid hemostasis, fat transport, and immune transport. In deep investigation in lymphatic function shows that alteration in lymphatic vessel could disrupt normal cardiovascular function. Moreover, optimal cardiac lymphatic condition after post-heart tissue injury could enhance tissue regeneration. That is why in modern medicine era preserving optimal lymphatic condition and treat abnormal lymphatic condition might be beneficial in cardiovascular medicine.